2017
DOI: 10.1007/s00266-017-0776-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance of Poly Implant Prosthesis (PIP) Breast Implants: A Comparative Study

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…These findings suggest a lack of chemical degradation during the implantation time. The new peak (2025 cm 21 ) found in the spectra from Pa10 shows that the gel did absorb mesoporous silica compounds. These compounds are widely used as catalysts for drug delivery reagents and imaging [32,33].…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…These findings suggest a lack of chemical degradation during the implantation time. The new peak (2025 cm 21 ) found in the spectra from Pa10 shows that the gel did absorb mesoporous silica compounds. These compounds are widely used as catalysts for drug delivery reagents and imaging [32,33].…”
Section: Discussionmentioning
confidence: 95%
“…In the literature, shell thickness variations have already been identified as one of several factors that may affect the integrity of the shell [15,21]. In a previous work, the authors concluded that shell thickness may play a role in the process of implant failure, with thinner implants displaying lower tensile strengths [21]. For example, for Pa04's ruptured implant specimens, the authors found that 0.63 mm of thickness corresponded to 7 MPa stress, and 1.0 mm corresponded to 11 MPa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations